2018
DOI: 10.1103/physrevb.98.224507
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced metastable state with modulated Josephson coupling strengths in Pr0.88LaCe0.12CuO4

Abstract: Photoexcitations on a superconductor using ultrafast nir-infrared (NIR) pulses, whose energy is much higher than the superconducting energy gap, are expected to suppress/destroy superconductivity by breaking Cooper pairs and excite quasiparticles from occupied state to unoccupied state far above the Fermi level. This appears to be true only for small pumping fluence. Here we show that the intense NIR pumping has different effect. We perform an intense NIR pump, c-axis terahertz probe measurement on an electron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The interpretation of these data is, however, still under intense discussion, ranging from aspects of the data analysis to the different interpretations of the origin of the light-induced modifications of low frequency σ (ω) [126][127][128][129][130][131][132][133][134]. Recently, several groups performed similar studies of the c-axis THz response using both mid-infrared as well as near-infrared pulses for photoexcitation [125,128,129,[135][136][137]. While it was demonstrated that near-infrared excitation results in similar changes in the low frequency conductivity as with mid-infrared excitation [135,137],…”
Section: Photo-induced Superconductivity In Unconventional Supercondu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The interpretation of these data is, however, still under intense discussion, ranging from aspects of the data analysis to the different interpretations of the origin of the light-induced modifications of low frequency σ (ω) [126][127][128][129][130][131][132][133][134]. Recently, several groups performed similar studies of the c-axis THz response using both mid-infrared as well as near-infrared pulses for photoexcitation [125,128,129,[135][136][137]. While it was demonstrated that near-infrared excitation results in similar changes in the low frequency conductivity as with mid-infrared excitation [135,137],…”
Section: Photo-induced Superconductivity In Unconventional Supercondu...mentioning
confidence: 99%
“…1.905 Ba 0.095 CuO 4[135], La 1.885 Ba 0.115 CuO 4[125], and Pr 0.88 LaCe 0.12 CuO 4[136], however reported a photoinduced red shift of the JPR and the appearence of an additional mode at higher frequencies. While at temperatures above T c no such photoinduced mode was observed in La 1.905 Ba 0.095 CuO 4[135], it has been observed in La 1.885 Ba 0.115 CuO 4 , albeit at very high excitation density of 9 mJ/cm 2[125].…”
mentioning
confidence: 99%
“…The control of electronic order via nonequilibrium drive is a problem of fundamental importance and great current interest [1][2][3][4][5][6][7][8][9] . One recently studied situation is the case of competing orders, where a nonequilibrium drive may suppress the order which is dominant in equilibrium, potentially allowing a different order, not observed in equilibrium, to arise.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments [1][2][3][4][5]7,8 and theoretical analyses 6,10-12 have addressed the situation in which a nonequilibrium drive pulse transiently drives the entire system into a disordered phase. After the drive ceases, order will re-form and depending on the dynamics an intermediate time regime may occur in which the system evolves to the local free energy minimum corresponding to a subdominant metastable phase 6 , before the system finally fully equilibrates.…”
Section: Introductionmentioning
confidence: 99%
“…Nicoletti et al reported a surprisingly large effect on La 2−x Ba x CuO 4 (x=0.115): a blue shift of JPE with even enhanced edge am-plitude when T<T c , and a light-induced edge when T>T c in the stripe ordered state whose amplitude is comparable with that seen in the equilibrium superconducting state 14,15 . Significant NIR pump-induced effect was recently also observed in time-resolved THz measurement on other compositions of La 1−x A x CuO 4 (A=Ba, Sr) and electron-doped Pr 1−x LaCe x CuO 4 [16][17][18][19][20] . Those results are notably different from the above reports on La 1.8−x Eu 0.2 Sr x CuO 4 4 and YBa 2 Cu 3 O 6.5 5,6 , where the relative change of reflectivity is less than 20% even after taking the penetration depth mismatch into account.…”
mentioning
confidence: 96%